Diarrhea in Critically ill Patients: Evaluation and Management in the Intensive Care Unit - Marwan N. Hassan (Journal of Intensive Care Medicine, 2026)
Objective Diarrhea is a common and clinically significant problem in critically ill patients, often reflecting underlying gastrointestinal dysfunction, systemic illness, or iatrogenic factors. The study aims to provide a practical framework for intensivists to identify, evaluate, and manage diarrhea in the critically ill patients, emphasizing its clinical significance, diagnostic approach, and management strategies. Methods This review synthesizes current evidence on the epidemiology, pathophysiology, and risk factors of ICU diarrhea. Life-threatening and non-life-threatening causes are discussed, including Clostridioides difficile infection, acute mesenteric ischemia, critical illness–associated diarrhea, drug-induced diarrhea, and enteral nutrition–related diarrhea. Diagnostic strategies, including bedside assessment, stool testing, and imaging, are outlined, alongside therapeutic approaches prioritizing fluid and electrolyte balance, modification of iatrogenic triggers, and optimization of enteral nutrition. Results ICU diarrhea is associated with increased morbidity, fluid and electrolyte disturbances, malnutrition, skin breakdown, secondary infections, prolonged ICU stay, and higher healthcare costs. Early recognition, systematic evaluation, and a structured management plan can reduce complications and maintain enteral nutrition. Conclusion Diarrhea in critically ill patients is a marker of gut dysfunction and systemic instability. A multidisciplinary, evidence-based approach is essential to improve outcomes, prevent complications, and optimize nutritional support.